Estimation of the Torsional Rigidity of Orthotropic Solid Cross Section - ECSEDI, István; BAKSA, Attila (Engineering Transactions, 2021)
In this paper, two inequality relations are proven for the torsional rigidity of orthotropic elastic solid cross sections. By using the derived inequality relations, lower and upper bounds can be obtained for the torsional rigidity. All results of the paper follow from the Saint-Venant theory of uniform torsion. The presented bounding formulae are based on the mean value theorem of integral calculus.